The Influence of IT Capability on Operational Performance Through Internal and External Integration: Evidence from Indonesia - Hadikusuma, Steven; Siagian, Hotlan (Organizations and Markets in Emerging Economies, 2022)
During the Pandemic of COVID-19, many manufacturing companies around the world, such as Indonesia, experienced supply and demand disruption. The PMI index reflecting the operational performance declined to 27.5 in April 2020 from 45 in January 2020. This study investigates the influence of IT capability on operational performance through internal and external integration. The sample consists of 111 manufacturing companies, and data analysis adopts the Partial Least Square (PLS) approach with SmartPLS. The results revealed that nine hypotheses proposed were supported. First, IT capability directly affects internal, external integration, and operational performance. Second, internal and external integration affects operational performance. Third, IT capability indirectly affects operational performance through internal and external integration. This research paves a way on how to recover the operational performance during the pandemic. These findings also contribute to enriching and extending the acceptance of previous research in the manufacturing industry context.
Keywords: information technology capability; internal integration; external integration; operational performance